LIFE QUALITY AND MENTAL DISORDERS IN CANCER PATIENTS - I. Е. Kupriyanova; S. А. Tuzikov; Е. S. Gural (Сибирский онкологический журнал)
The review discusses the role of mental disorders in oncology practice, their types, prevalence and clinical features. Problems of using drugs and psychoactive substances as a factor in the development of mental disorders in cancer patients are also considered in this review. Studies showing clinical and psychological problems (pain, fear, anxiety) that reduce the quality of life in cancer patients have been presented. Results of pharmaco-and psychotherapy in relieving psychopathology are discussed.